STRATEGI PEMBELAJARAN (PJBL) AKTIF UNTUK MENINGKATKAN KETERLIBATAN SISWA DI SEKOLAH DASAR - Rizky Amaliya; Khodijatul Kubro (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to provide understanding to discuss the implementation of project-based learning (PjBL) strategies as an active method in increasing student involvement in elementary schools. This research uses the systematic literature review (LSR) research method. This data was obtained from various data sources through search, assessment and analysis from written and trusted sources. The research results show that Project-Based Learning (PjBL) is an innovative pedagogical approach that provides meaningful learning experiences through real project activities. This strategy allows students to develop complex skills such as critical thinking, collaboration, and problem solving directly in an authentic learning context. Through PjBL, students do not just receive passive information, but actively design, explore and complete challenging projects according to the expected competencies. Implementing the PjBL strategy requires systematic planning from educators. Teachers act as facilitators who design learning projects that are challenging but still appropriate to the developmental stages of elementary school students. The main challenge in implementing PjBL is teacher competence in designing and guiding the learning process.